The life cycle environmental impacts of a novel sustainable ammonia production process from food waste and brown water. (20th October 2021) - Ghavam, Seyedehhoma; Taylor, Caroline M.; Styring, Peter
Abstract: To replace existing high impact ammonia production technologies, a new sustainability-driven waste-based technology producing green ammonia with and without urea was devised using life cycle thinking and sustainable design principles, targeting efficiency, carbon emissions, water, and power use competitiveness. We have used life cycle assessment to determine whether cradle-to-gate, multiple configurations of the core waste-based processes integrating several carbon capture/utilization options can compete environmentally with other available ammonia technologies. Our waste-to-ammonia processes reduce potential impacts from abiotic depletion, human toxicity, and greenhouse gas (GHG) emissions relative to fossil-based and renewable technologies. Among the assessed technologies, coupling dark fermentation with anaerobic digestion and capturing CO2 for sequestration or later use is most efficient for GHGs, water, and energy, consuming 27% less energy and reducing GHGs by 98% compared to conventional ammonia. Water use is 38% lower than water electrolysis and GHGs are 94% below municipal waste incineration routes per kg NH3 . Additionally, displacing conventional, high impact urea by integrating urea production from process CO2 decreases life cycle environmental impacts significantly despite increased energy demand. On a fertilizer-N basis, the ammonia + urea configuration without dark fermentation performs best on all categories included. Methane and ammonia leakage cause nearly all life cycle impacts, indicating that failing to prevent leakage undermines the effectiveness of new technologies such as these. Our results show that a green ammonia/ammonia + urea process family as designed here can reduce waste and prevent the release of additional CO2 from ammonia production while avoiding fossil-based alternatives and decreasing emissions from biogenic waste sources.